Steering Feel Design: The Effect of Mass Variation - Kirli, Ahmet; Arslan, M. Selcuk (ELSEVIER, 2016)
In rubber-wheeled road vehicles, the torque fed back to the driver through the steering linkages and steering wheel, which is called steering feel, helps the driver in controlling the vehicle. The torque feedback is reproduced via artificial methods in steer-by-wire systems due to the lack of mechanical connection. Since the mass of vehicle is one of the essential parameters in the dynamics of vehicle, its effect on the steering feel and on the design of steering feel model needs to be discussed. This study investigates the design of steering feel model so as to involve the mass variation. The novelty of this study is to design a steering feel not to mimic the steering feel of any conventional vehicle, but to search the optimum steering feel value. A 2-DOF bicycle model with the Magic formula tire model was used in the simulations and HIL experiments. The steering feel model was tested with different mass scenarios according to the ISO standard weave test. A HIL experimental setup was used for the driving tests. The weave test has been performed with different drivers in order to evaluate the behavior of the model under mass variation. (C) 2016, IFAC (International Federation of Automatic Control) Hosting Elsevier Ltd. All rights reseirved.
Keywords: steering feel; steer-by-wire hysteresis; physical workload; optimization; mass variation; Automation & Control Systems